Effect of Inter-Domain Linker Composition on Biodistribution of ABD-Fused Affibody-Drug Conjugates Targeting HER2 - Tianqi Xu; Jie Zhang; Maryam Oroujeni; Maria S. Tretyakova; Vitalina Bodenko; Mikhail V. Belousov; Anna Orlova; Vladimir Tolmachev; Anzhelika Vorobyeva; Torbjörn Gräslund (MDPI AG, 2022)
Targeted drug conjugates based on Affibody molecules fused to an albumin-binding domain (ABD) for half-life extension have demonstrated potent anti-tumor activity in preclinical therapeutic studies. Furthermore, optimization of their molecular design might increase the cytotoxic effect on tumors and minimize systemic toxicity. This study aimed to investigate the influence of length and composition of a linker between the human epidermal growth factor receptor 2 (HER2)-targeted affibody molecule (ZHER2:2891) and the ABD domain on functionality and biodistribution of affibody-drug conjugates containing a microtubulin inhibitor mertansin (mcDM1) (AffiDCs). Two conjugates, having a trimeric (S3G)3 linker or a trimeric (G3S)3 linker were produced, radiolabeled with 99mTc(CO)3, and compared side-by-side in vitro and in vivo with the original ZHER2:2891-G4S-ABD-mcDM1 conjugate having a monomeric G4S linker. Both conjugates with longer linkers had a decreased affinity to HER2 and mouse and human serum albumin in vitro, however, no differences in blood retention were observed in NMRI mice up to 24 h post injection. The use of both (S3G)3 and (G3S)3 linkers reduced liver uptake of AffiDCs by approximately 1.2-fold compared with the use of a G4S linker. This finding provides important insights into the molecular design for the development of targeted drug conjugates with reduced hepatic uptake.